2021
DOI: 10.1088/1755-1315/765/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper and Magnesium Cations from Aqueous Solutions by Clinoptilolite Zeolite Adsorption

Abstract: The aim of this study is to determine the potentials of clinoptilolite zeolite in removing selected heavy metals, that are copper and magnesium in aqueous solutions. The removal of both metal cations has been studied by using the batch techniques. Three experimental variables were carried out under predetermined conditions of contact time (20 – 100 minutes), effect of dosage (0.20 – 1.00 gram), and effect of pH solution (pH 2 to 10). Adsorption capacity of zeolite towards heavy metal removal was then determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This may be due to it reduces H⁺ on the adsorbent surface, which increases the surface's negative charge and boosts the adsorbent's ability to bind metal ions [13]. The aforementioned result is consistent with the outcomes reported by Aziz et al [11], Pavan Kumar et al [14], and El-Azim and Mourad [15], which state that when the pH value (1) increases, then the percentage of copper removal using zeolite also increases. The result of optimum pH 6 was chosen for the removal of copper using zeolite.…”
Section: Ph Of Copper Solutionsupporting
confidence: 85%
See 2 more Smart Citations
“…This may be due to it reduces H⁺ on the adsorbent surface, which increases the surface's negative charge and boosts the adsorbent's ability to bind metal ions [13]. The aforementioned result is consistent with the outcomes reported by Aziz et al [11], Pavan Kumar et al [14], and El-Azim and Mourad [15], which state that when the pH value (1) increases, then the percentage of copper removal using zeolite also increases. The result of optimum pH 6 was chosen for the removal of copper using zeolite.…”
Section: Ph Of Copper Solutionsupporting
confidence: 85%
“…There was a modest and gradual improvement in the removal of copper as the dosage of adsorbent increased due to the greater availability of exchangeable sites or surface area [10]. The number of zeolite adsorption sites or surface area increases with the increased weight of the adsorbent, causing a more effective metal removal after the experiment and permitting easier adsorbate penetration into the adsorption sites [11]. The results obtained in this study also align with the outcomes reported by Zendelska et al [7] and Meena et al [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics make the clinoptilolite particularly suitable for adsorption of metals from wastewater. Many researchers have previously used this material to treat aqueous systems polluted with different metals in batch mode, such as Zn 2+ , Cu 2+ , Pb 2+ , or Cd 2+ , among others [12][13][14][15][16]. However, the utilization of clinoptilolite in fixed bed has not been widely used, only to remove metals like Mn 2+ , Cr 3+ , Cd 2+ , and Zn 2+ [17,18] and, more specifically, the use of clinoptilolite to remove gallium has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%